Meditation in association with psychosis - Chan-Ob T. (2014)
This study analysed the correlation between contemplation and psychosis from three cases of patients presenting psychotic symptoms subsequent to practising meditation. Sleep loss following a wrong doing in meditation was found to be the main cause in the first two cases, and drug withdrawal was found to be the principal factor in causing a psychotic eruption in the third case. In this last case, sleep deprivation subsequent to meditation was only a minor influence. Discussion regarding the correlation between meditation and psychosis is presented in this study.